Ultra‐deep sequencing analysis of resistance‐associated variants during retreatment with simeprevir‐based triple therapy after failure of telaprevir‐based triple therapy in patients with genotype 1 hepatitis C virus infection. Issue 8 (26th October 2016) - Morishita, Naoki; Hiramatsu, Naoki; Oze, Tsugiko; Urabe, Ayako; Tahata, Yuki; Yamada, Ryoko; Yakushijin, Takayuki; Hosui, Atsushi; Iio, Sadaharu; Yamada, Akira; Hagiwara, Hideki; Mita, Eiji; et al.
Abstract : Aim: Simeprevir (SMV)‐based triple therapy is an effective retreatment option following failure of telaprevir (TVR)‐based triple therapy. However, it is unclear whether the persistence of resistance‐associated variants (RAVs) induced by TVR‐based therapy may reduce the treatment effect of SMV‐based therapy. Methods: The factors associated with the treatment effect, including RAVs in the NS3 region, were examined in 21 patients with genotype 1b HCV infection who were treated with SMV‐based therapy after failure of TVR‐based therapy. Ultra‐deep sequencing was carried out to detect RAVs. Results: With the exception of one patient who discontinued treatment owing to adverse events, the sustained virologic response (SVR) rate was 50% (10/20). Ultra‐deep sequencing at the start of SMV‐based therapy revealed that TVR‐resistant variants were detected in six patients (29%), and no variants were observed at position 168. Cross‐resistance between TVR and SMV with low frequency was detected in only one patient, and this patient achieved SVR. Higher SVRs for SMV‐based therapy were attained in patients who discontinued treatment owing to the adverse effects of prior TVR‐based therapy (discontinuation 100% vs. non‐discontinuation 29%, P  = 0.005), and patients who relapsed following prior pegylated interferon plus ribavirin therapy (relapse 100% vs. non‐response 20%, P  = 0.007). Conclusions: In this study, ultra‐deep sequencing analysis revealed that TVR and/or SMV‐resistant variants may have no influence on the effect of SMV‐based therapy after failure of TVR‐based therapy. Patients who discontinued treatment owing to adverse effects of TVR‐based therapy and relapsers to previous pegylated interferon/ribavirin therapy would be good candidates for retreatment with SMV‐based therapy.